Meaningful Ethnoscience Integrated Problem-Based Learning for Analytical Thinking and Curiosity - Pradana, Sendy Putra; Nurdiana, Herning; Antony, Muhammad Khoirul; Ramadhan, Ahmad Naharuddin; Sianturi, Advend Sri Rizki (Jurnal VARIDIKA, 2026)
This study aimed to examine the effectiveness of Problem-Based Learning (PBL) integrated with meaningful learning and ethnoscience in enhancing analytical thinking and curiosity among junior high school students. The study was motivated by low student engagement and the dominance of conventional teacher-centered instruction that lacks contextualization and incorporation of local knowledge. A quantitative quasi-experimental design with a non-equivalent control group was employed, involving 60 eight-grade students divided into experimental and control classes. Analytical thinking was assessed through a validated essay test, while curiosity was measured using an observation checklist, both demonstrating adequate validity and reliability. Data analysis included normality and homogeneity tests, independent samples t-tests, and Pearson correlation. Results indicated a significant improvement in analytical thinking in the experimental class compared to the control (t = –33.289, p < .001), and curiosity was also significantly higher (t = –20.079, p < .001). Furthermore, a strong positive correlation was found between analytical thinking and curiosity (r = 0.801, p < .001), indicating that curiosity accounts for approximately 64.16% of the variance in analytical thinking. These findings confirm that integrating PBL, meaningful learning, and ethnoscience effectively improves students’ analytical thinking, as indicated by a high N-Gain in the experimental class (0.703) compared to a low N-Gain in the control class (0.206), and increases students’ curiosity, as shown by higher posttest mean scores in the experimental group than in the control group. The study implies that educators should adopt problem-based learning contextualized with local knowledge to improve science learning quality and 21st-century competencies.